2020
DOI: 10.1177/1553350620967853
|View full text |Cite
|
Sign up to set email alerts
|

The LOCalizer Radiofrequency Identification System: An Effective New Technology for Localizing Non-Palpable Breast Lesions for Surgery

Abstract: Background. Breast screening has decreased morbidity and mortality due to detection of early, non-palpable breast cancers. One of the challenges of performing breast-conserving surgery on non-palpable breast tumours is accurate localization of the cancer. We aimed to perform a feasibility study to examine the outcomes associated with the introduction of a novel radiofrequency identification system (RFID) called LOCalizer as an alternative to traditional wire-guided localization. Methods. Data were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The study design of the included studies was prevalently prospective (18, 66,7%), involving from 4 to 320 patients each. The devices used in the studies were: SAVI SCOUT (9, 33.3%) [ [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ], Magseed (10, 37%) [ 38 , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ], Localizer (5, 18.5%) [ 38 , 40 , [51] , [52] , [53] , [54] , [55] ] and MaMaLoc (1, 3.7%) [ 56 ]. One study reported results about the use of both Magseed and LOCalizer [ 38 ] and in one both SAVI SCOUT and LOCalizer were used [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design of the included studies was prevalently prospective (18, 66,7%), involving from 4 to 320 patients each. The devices used in the studies were: SAVI SCOUT (9, 33.3%) [ [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ], Magseed (10, 37%) [ 38 , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ], Localizer (5, 18.5%) [ 38 , 40 , [51] , [52] , [53] , [54] , [55] ] and MaMaLoc (1, 3.7%) [ 56 ]. One study reported results about the use of both Magseed and LOCalizer [ 38 ] and in one both SAVI SCOUT and LOCalizer were used [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hematoma has been reported (up to 19%): after biopsy [ 34 , 38 ] (leading also to a possible difficulty in obtaining the signal from the device [ 34 ]), following the localization [ 48 ], and post operatively [ 33 , 39 , 49 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Full texts were then examined for the 10 abstracts, which met the inclusion criteria for our review [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. One study (Tayeh et al) [ 10 ] was excluded since its results were part of a larger study that is already included in our analysis [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nine studies were used in the final analysis. Seven cohort studies used to calculate the rates of successful placement, successful retrieval and re-excision in the final pooled analysis [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Technological advancements in the surgical management of non-palpable breast lesions such as wire-free radar technology to provide real-time surgical guidance during breast surgery have demonstrated efficacy and are oncologically safe ( 108 , 109 ). The emergence of imaging and probe-based devices to detect differences between normal and cancerous tissue have the potential to improve margins, reduce re-operation rates and avoid current labour-intensive intraoperative margin assessment techniques such as frozen section and specimen radiology.…”
Section: Future Perspective On Breast Cancer Surgerymentioning
confidence: 99%